Factors Influencing Parental Consent in a Hypothetical Pediatric Vaccine Trial in a Developing Country Setting: A Questionnaire Study - (:unkn) unknown (TAYLOR & FRANCIS INC, 2015)
Clinical vaccine trials have been lacking in the pediatric population due to lower consent rate of the parents. We assessed characteristics of the parents, and motives and barriers underlying the decision process. The results of the questionnaire were evaluated by multivariate analysis. Parents who opted in were younger and more often employed than the parents who opted out. The most important motives were receiving detailed information about trial and benefits to human health. The qualified education of medical community and public about the rationale and benefits of trials is essential for opt-in.
Keywords: trial; consent; vaccine; child; CLINICAL-RESEARCH; CHILDREN; PARTICIPATION; VOLUNTEER